(untitled) (Bangladesh Journal of Medicine, 2019)
The occurrence of posterior reversible encephalopathy syndrome (PRES) in patients with eclampsia is a rare condition. PRES is a reversible syndrome characterized by headache, seizure, altered mentation and loss of vision associated with white matter changes on imaging. The lesions in PRES are thought to be due to vasogenic oedema, predominantly in the posterior cerebral hemispheres. This study reports a 32-year-old pregnant woman who presented with headache, dimness of vision, right sided weakness and seizure. The MRI of her brain showed abnormal signal intensity in the white matter of the occipital and parietal lobes. She was treated successfully with pregnancy termination, anti-hypertensives, anticonvulsants, and supportive care. It is concluded that early diagnosis is important to prevent permanent neurologic damage and mortality. Bangladesh J Medicine July 2019; 30(2) : 104-107